Measuring progress toward universal health coverage: Does the monitoring framework of Bangladesh need further improvement? - Gupta, Rajat Das; Shahabuddin., ASM (Cureus, 2022)
This article was published in the Cureus [© 2018 open access article distributed under the terms of the Creative Commons Attribution License CC-BY 3.0. ] and the definite version is available at : https://doi.org/10.7759/cureus.2041 The Journal's website is at: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5843382/